Growth Hormone-Releasing Hormone and Its Analogues: Significance for MSCs-Mediated Angiogenesis - Xiangyang Xia; Quanwei Tao; Qunchao Ma; Huiqiang Chen; Jian’an Wang; Hong Yu (Stem Cells International)
Mesenchymal stromal cells (MSCs) are promising candidates for regenerative medicine because of their multipotency, immune-privilege, and paracrine properties including the potential to promote angiogenesis. Accumulating evidence suggests that the inherent properties of cytoprotection and tissue repair by native MSCs can be enhanced by various preconditioning stimuli implemented prior to cell transplantation. Growth hormone-releasing hormone (GHRH), a stimulator in extrahypothalamus systems including tumors, has attracted great attentions in recent years because GHRH and its agonists could promote angiogenesis in various tissues. GHRH and its agonists are proangiogenic in responsive tissues including tumors, and GHRH antagonists have been tested as antitumor agents through their ability to suppress angiogenesis and cell growth. GHRH-R is expressed by MSCs and evolving work from our laboratory indicates that treatment of MSCs with GHRH agonists prior to cell transplantation markedly enhanced the angiogenic potential and tissue reparative properties of MSCs through a STAT3 signaling pathway. In this review we summarized the possible effects of GHRH analogues on cell growth and development, as well as on the proangiogenic properties of MSCs. We also discussed the relationship between GHRH analogues and MSC-mediated angiogenesis. The analyses provide new insights into molecular pathways of MSCs-based therapies and their augmentation by GHRH analogues.